KEANEKARAGAMAN FLORA DI TAMAN NASIONAL BUKIT BARISAN SELATAN, PROVINSI LAMPUNG - Deby Arifiani; Ridha Mahyuni (BERITA BIOLOGI, 2012)
Study on plant diversity by exploration and collection have been carried out at the Bukit Barisan Selatan National Park, Province of Lampung.The study sites was focused on secondary lowland forests of Way Canguk and Sukaraja Atas. The research was aimed to obtain floristic data from such areas that has never been recorded. Flora diversity in these areas is relatively high as represented by 183 plant species from 124 genera and 60 families. It is noted that 3 species are newly for Sumatran flora.